2022
DOI: 10.3390/molecules27061759
|View full text |Cite
|
Sign up to set email alerts
|

A New and Sensitive HPLC-UV Method for Rapid and Simultaneous Quantification of Curcumin and D-Panthenol: Application to In Vitro Release Studies of Wound Dressings

Abstract: Curcumin (CUR) and D-panthenol (DPA) have been widely investigated for wound-healing treatment. In order to analyse these two compounds from a dosage form, such as polymer-based wound dressings or creams, an analytical method that allows the quantification of both drugs simultaneously should be developed. Here, we report for the first time a validated high-performance liquid chromatographic (HPLC) method coupled with UV detection to quantify CUR and DPA based on the standards set by the International Council o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 36 publications
1
3
0
Order By: Relevance
“…The precision, which indicates the method’s repeatability, exhibited an RSD% value from 0.98 to 3.06%, within the concentration range tested. The results confirmed that the new analytical method is accurate and precise since the values obtained were lower than the acceptable value of 15%; hence, they are under the recommendations for bioanalytical methods [ 60 , 66 , 67 ]. Based on these results, it can be assumed that the current approach is potentially appropriate for quantifying RB deposited into skin samples.…”
Section: Resultssupporting
confidence: 60%
“…The precision, which indicates the method’s repeatability, exhibited an RSD% value from 0.98 to 3.06%, within the concentration range tested. The results confirmed that the new analytical method is accurate and precise since the values obtained were lower than the acceptable value of 15%; hence, they are under the recommendations for bioanalytical methods [ 60 , 66 , 67 ]. Based on these results, it can be assumed that the current approach is potentially appropriate for quantifying RB deposited into skin samples.…”
Section: Resultssupporting
confidence: 60%
“…The in vitro release profiles of coarse CUR, PM, CUR NCs and Egel-20-NCs were assessed using a dialysis membrane model according to a previously described methodology [ 27 , 28 ]. The release media consisted of 100 ​mL of 2% w/v Tween® 80 in buffer saliva pH 6.4 containing 0.5% w/v of ascorbic acid to prevent drug degradation [ 29 ]. For this experiment, 2.6 ​mg of CUR powder and CUR NCs (containing 1.97 ​mg of CUR) were placed in dialysis membrane bags of 12,000–14,000 ​kDa molecular weight cut-off (MWCO) (Spectra-Por, Spectrum Medical Industries, Los Angeles, CA, U.S.A.) and sealed at both ends with clips.…”
Section: Methodsmentioning
confidence: 99%
“…Metrics like relative standard deviation (RSD) (eqn (3)), repeatability, and intermediate precision were computed based on the estimated concentrations. 55 For concentrations under analysis, an RSD value lower than 10% is considered acceptable. 52,56 …”
Section: Methodsmentioning
confidence: 99%